2005
DOI: 10.1074/jbc.m500997200
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Dysregulation and Membrane Disruption as a Ubiquitous Neurotoxic Mechanism of Soluble Amyloid Oligomers*♦

Abstract: Increasing evidence suggests that amyloid peptides associated with a variety of degenerative diseases induce neurotoxicity in their intermediate oligomeric state, rather than as monomers or fibrils. To test this hypothesis and investigate the possible involvement of Ca 2؉ signaling disruptions in amyloid-induced cytotoxicity, we made homogeneous preparations of diseaserelated amyloids (A␤, prion, islet amyloid polypeptide, polyglutamine, and lysozyme) in various aggregation states and tested their actions on f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

59
869
1
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 932 publications
(935 citation statements)
references
References 49 publications
59
869
1
6
Order By: Relevance
“…This channel formation disrupts cellular ionic homeostasis such as Ca 2þ influx. In agreement with this report, only Ab oligomers (not fibrils and monomeric forms) increased intra-cellular Ca 2þ (Demuro et al, 2005). First pioneered by Arispe et al (1993), this mechanism is now commonly referred to as the b-amyloid calcium channel hypothesis after its inception in 1994 (Arispe et al, 1994).…”
Section: Lipid Modulation Of Amyloid Beta Aggregation and Neurotoxicitysupporting
confidence: 89%
“…This channel formation disrupts cellular ionic homeostasis such as Ca 2þ influx. In agreement with this report, only Ab oligomers (not fibrils and monomeric forms) increased intra-cellular Ca 2þ (Demuro et al, 2005). First pioneered by Arispe et al (1993), this mechanism is now commonly referred to as the b-amyloid calcium channel hypothesis after its inception in 1994 (Arispe et al, 1994).…”
Section: Lipid Modulation Of Amyloid Beta Aggregation and Neurotoxicitysupporting
confidence: 89%
“…As a result of this work, it has been shown that dynamin 1 was significantly reduced not only in the hippocampus of an AD mouse model and in cultured hippocampal neurons treated with Aβ but also in the brain of AD patients (Yao et al 2003;Kelly et al 2005;Kelly and Ferreira 2006). The mechanisms leading to this dynamin 1 depletion seem to involve calpain, a protease system that is active in AD (Tsuji et al 1998;Lee et al 2000;Battaglia et al 2003;Tomizawa et al 2003;Chen and Fernandez 2005;Demuro et al 2005;Gong et al 2005;Kelly et al 2005;Fifre et al 2006;Kelly and Ferreira 2006). Furthermore, we have reported that this Aβ-mediated dynamin 1 degradation was the result of calpain activation induced by the sustained calcium influx mediated by N-methyl-D-aspartate (NMDA) receptors in hippocampal neurons (Kelly and Ferreira 2006).…”
Section: Discussionmentioning
confidence: 73%
“…26 These can impair various signaling and synaptic functions of the neuron by influencing intracellular calcium levels and cellular membranes. 26,43 The role of ER in these processes remain to be studied in more detail.…”
Section: Er Stress and Admentioning
confidence: 99%